Mistreatment behaviours in the Athlete-coach relationship - Marracho, Philippe (2023)
This qualitative study aimed to describe the nature of mistreatment behaviours in the Athlete-coach relationship, in the region of Trás-os-Montes e Alto Douro, Portugal. For our study, we interviewed 12 athletes of federated sports. We focused on young athletes, aged 13-18 years old, who practiced a collective, combat, or individual sports discipline. The data was then studied through content analysis. In the case of athletes as victims, there were no mistreatment behaviours in the Athlete-coach relationship. However, as observers, the athletes have reported forms of abuse in the Athlete-coach relationship, such as verbal emotional abuse and denial of attention and support. As preventative measures for mistreatment behaviours, the athletes mentioned supervision and even the dismissal of the coach. Respondents stress the need to deepen the topic for the strategies to be effective. They emphasize the need to sensitize clubs for the protection of athletes, through investigations in the area under study, for fighting and preventing mistreatment behaviour in sports practice.